UPAYA MENINGKATKAN DAYA DUKUNG SUMBERDAYA AIR PULAU JAWA - Ikhwanuddin Mawardi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Water resource capacity in Java is significantly decreased. This has beennoticed by the more frequent floods and over-dried seasons happened inseveral locations in Java. On the other side, the water demand in Java israised as the result of increasing population and quality of live. Reducingof water resourcing capacity related with forest degradation, change ofland usage and river pollution. Interpretation of the satellite imaging in2005 showed that the vegetated land areas is left abaut 2,4 acre or 21%of the wholw area of Java island. This is lower than the regulatedrequirement, i.e. about 30%. Efforts might be needed to solve thisproblems, cover (1) Regulation of the number and distribution of population;(2) Forest and land rehabilitation; (3) Coasts degradation control; (4)Increasing efficiency of water usage and control of river pollution; (5)Management of land usage by implementing the required 30% area asopened green areas; and (6) Deregulation of the water managementinstitution.